THE MANAGEMENT OF COURSES AND TRAINING INSTITUTE (LKP) PUSPA KENCANA TO IMPROVE THE QUALITY OF STUDENTS' LEARNING - Dede Suryadi; Sri Nurhayati (IKIP Siliwangi Bandung, 2020)
This research aims to describe the management of computer courses and training at Puspa Kencana Course and Training Institute (LKP) to improve learning quality. The research method used is descriptive. The data collected in this study uses interviews, observation, documentation studies, and data triangulation techniques. The subjects of this study were LKP manager Puspa Kencana, instructors, and computer trainees selected purposively. The results showed that 1) Management starts with planning, which includes identifying learning needs, determining students, instructors, and preparing infrastructure facilities. 2) The implementation of the course program at Puspa Kencana is carried out on a scheduled and systematic basis by being given some additional materials to improve competency. 3) The training results show the students are independently able to carry out what they earn during computer course activities. 4) Efforts to improve learning quality are carried out by instructors who include teaching with sincere intentions, providing engaging learning by using methods, refracting questions to students, and instructors already attending workshop seminars to improve their abilities. 5) The supporting factor in the management of the course comes from external factors, namely, support from the local area to facilitate the implementation of courses. While the inhibitory factor comes from internal managers such as technical constraints such as equipment malfunction, irregular and unorderly maintenance of computers' components. Furthermore, if the administration is not well managed, then it will be an inhibition of many things such as not being able to pay salaries, and buying the operational needs of the institution